The effect of bubbling on the germination of Sudan grass seeds - Madiyeva, A.N.; Silantiyeva, M.M. (Fundamental and Experimental Biology, 2024)
In the article the results of experiments to study the effect of bubbling on the germination of Sudan grass seeds before and after cryopreservation were presented. The obtained statistical data were processed using the R-studio program. We calculated the indicators of humidity and germination energy of Sudan grass seeds, and determined the statistically reliable significance between the control and experimental varieties. To conduct the experiment, a bubbler installation was created from a cylindrical container filled with water and a bubbler to supply oxygen. The results of pre-sowing seed treatment were obtained for 4 varieties of Sudan grass: Nika, Tugai, Alina, Novosibirskaya 84. Bubbling increases seed germination compared to the control by 13 % for the Nika variety, by 7 % for the Novosibirskaya 84 variety. While bubbling after cryopreservation significantly reduces the germination of seeds in the Tugai variety by 25 %, in the Alina variety by 32 %, in the Novosibirskaya 84 variety by 33 %, and in the Nika variety by 7 %. Thus, bubbling, in general, had a positive effect on the germination of Sudan grass seeds and may be one of the methods of pre-sowing seed treatment. As a recommendation for improving the germination of Sudan grass seeds, we suggest using bubbling without cryopreservation.